Improvement of Village Productive Economy Through Village Funds Financing - Imran Rosman Hambali; Idris Yanto Niode (International Journal of Applied Business and International Management, 2019)
This study aims at finding out the actual condition of community empowerment activity and improvement of productive economic activities through village funds financing and gaining information on Village Funds management to increase productive economy in the village level. This is a descriptive study with a qualitative approach using Milles and Huberman as its method of analysis. This study finds that village funds financing is able to improve people’s welfare. This is evident from various achievement of the government of Bone Bolango regency. The success of this village funds in improving people’s welfare has made the central government to increase the village allocation funds for this regency annually. This village allocation fund is distributed through two channels: 1) direct disbursement for productive economic activities (grant), (2) fund disbursement for productive economic activity through Village Owned Enterprise (Hereinafter will be referred as BUMDes). To optimize this village funds management, several strategic steps such as: 1) increasing the capacity of village institution; 2). Establishment of Business Units as a joint working group needs to be done.